THE EFFECT OF CHEMICAL ADDITION FACTORS ON EXTERNAL WATER PURIFICATION WITH MICROSOFT EXCEL APPLICATION - Harahap, Bonar; Rahman, Aditya; Arfah, Mahrani (UIN Sumatera Utara, 2022)
This study aims to see the influence of chemical addition factors such as Alum, Soda ash, and Flocculand in external water treatment on water purification that will be used in processing in palm oil mills does not form scale / sediment on the walls, especially at boiler stations / boilers. This study was conducted in the laboratory using jartes with each triplo experiment / 3 times with the addition of a predetermined chemical dose and seen the turbidity / level of clarity and recorded processed into data. Then the results of the recapitulation of the research data obtained will be processed using the statistical analysis method using the complete random design (RAL) method of 3 factorials and continued with the results of the anova / fingerprint test table and the data processing will use the help of the Microsoft Excel application. From the results of the research obtained using the RAL (Complete Random Design) method 3 factorials the result that the influence of the addition of alum and flocculant chemicals will have a real effect on water purification which means that the Fhitung > Ftabel value, then Ho is rejected, alum and flocculants have the function of forming flocs that aim to precipitate dirt so that the water can be purified, it is very dominantly needed, While on the addition of chemical soda ash with the result of the decision obtained F count 0.186746989 < F table 3.168245967 So it can be concluded that Ho is accepted at the real level of ά. which means that the treatment has no real effect on the observed response. This is because soda ash has a function that can only be used as a pH regulator for the water to be purified in the palm oil mill.